Studi Teologi Akhir Zaman (Eskatologi) dan Signifikansinya bagi Orang Percaya - Siregar, Jonri Muksen (STT IKSM SANTOSA ASIH, 2024)
Abstract: The study of the end times has so much debate in the history of the church that is about the future. This greatly affects the correct view or understanding of what is in the Bible by each individual congregation. Such an understanding of the end times is important if you are to gain a correct understanding of eschatological theology or Christian theology as a whole. Many theologians seek to highlight all major aspects of theology as if they relate to the end times. This research uses qualitative methods which are a research procedure that produces descriptive data carried out by approaching someone or something in oral or written form. The authors use descriptive research that places more emphasis on the analysis of existing sources and data as key instruments. After the fall of man into sin (Gen. 3), it resulted in a very far-reaching impact, both on man himself and on the universe, among others; man is separated from God corrupt (Gen. 3:7, 10), spiritual death (Gen. 3:8-13), a sinful heart passed down to all mankind (Gen. 4:5,8), judgment will be inflicted upon all mankind (Rom. 5:12), physical death (Gen. 3:19, 22-24). The significance of physical death for mankind in general is as a decree (Heb. 9:27), and as a source of fear for Satan (Heb. 2:14-15). For the unbeliever, that there is no longer any time for the betterment of his life (Is. 22:13; Lu. 12:16-21; 1Cor. 15:32) and toward god's path of judgment (Rev. 20:11-15). For believers the significance is that the fear of death is lost, having been freed from the influence of the sting of death, which is eternal death (Rom. 8:2; 1Cor. 3:21-23). The signs that occurred do not give us an idea or ability to know the date of Christ's return. A correct understanding of eschatology will encourage every believer in the mission of evangelism to the end of the earth. Abstrak: Studi tentang akhir zaman mengalami begitu banyak perdebatan sering terjadi dalam sejarah gereja yakni mengenai masa depan. Hal ini sangat berpengaruh pada pandangan atau pemahaman yang benar sesuai yang ada di dalam Alkitab oleh setiap individu jemaat. Pemahaman tentang akhir zaman demikian penting jika ingin memperoleh pemahaman yang benar mengenai teologi eskatologi atau teologi Kristen secara keseluruhan. Banyak para teolog berusaha menyoroti semua aspek teologi utama seolah-olah berhubungan dengan akhir zaman. Penelitian ini menggunakan metode kualitatif yang merupakan sebuah prosedur penelitian yang menghasilkan data deskriptif yang dilakukan dengan pendekatan terhadap seseorang atau sesuatu dalam bentuk lisan ataupun tulisan. Penulis menggunakan penelitian deskriptif yang lebih menekankan pada analisis sumber dan data yang ada sebagai instrumen kunci. Setelah kejatuhan manusia kedalam dosa (Kej. 3), mengakibatkan dampak yang sangat luas, baik ke manusia itu sendiri maupun kepada alam semesta, antara lain; manusia terpisah dengan Allah rusak Kejadian 3:7, 10), kematian rohani (Kej. 3:8-13), hati yang berdosa diturunkan kepada seluruh umat manusia (Kej. 4:5,8), penghakiman akan ditimpakan kepada seluruh umat manusia (Romo 5:12), kematian fisik (Kej. 3:19, 22-24). Signifikansi kematian fisik bagi umat manusia secara umum adalah sebagai ketetapan (Ibr. 9:27), dan sebagai sumber ketakutan bagi Iblis (Ibr. 2:14-15). Bagi orang tidak percaya, bahwa tidak ada lagi waktu untuk perbaikan atas hidupnya (Yes. 22:13; Lu. 12:16-21; 1Kor. 15:32) dan menuju jalan penghakiman Allah (Why. 20:11-15). Bagi orang percaya signifikansinya adalah ketakutan akan kematian menjadi hilang, karena telah dimerdekakan dari pengaruh sengat maut yakni kematian kekal (Rm. 8:2; 1Kor. 3:21-23). Tanda-tanda yang terjadi tidak memberikan gambaran atau kemampuan bagi kita untuk mengetahui tanggal kedatangan Kristus kembali. Pemahaman eskatology yang benar akan mendorong setiap orang percaya dalam misi penginjilan sampai keujung bumi.